Demystifying the Forest Revenue and Policy Spillovers in the Utilization of Softwoods in Nepal - Dangi, Resham Bahadur (Banko Janakari, 2025)
Investigating forest revenue sources, timber auction rules, the spillover effects of trade policies on wood product demand, and import and export trends, this paper explores the influence of sectoral policies on the utilization of softwoods. Acknowledging the relative advantages of veneer and plywood exports, it suggests taking promotional measures to enhance the supply of required input products in partnership with other national policies. Analyzing wood product export trends, drawing on the authors’ professional experience, raises doubts about the export competitiveness of hardwoods. It concludes by suggesting that concerned authorities revisit the cost centers of hardwood production, adopting a transparent mechanism and ensuring ownership of outcomes.